Operating performance of external non-involute spur and helical gears - Okorn, Ivan (Strojniški vestnik, 2021)
In practical use, most gears have an involute shape of tooth flanks. However, external involute gears have some drawbacks, such as unfavourable kinematic conditions at the beginning and end of meshing, a limited minimum number of teeth, and the highly loaded convex-convex (i.e., non-conformal) contact. Researchers have developed and analysed various non-involute forms of tooth flanks, but they have not been widely accepted. The main reasons are higher manufacturing costs and sensitivity to manufacturing and assembly errors. Analyses of non-involute forms of teeth are mostly theoretical (analytical and numerical), while there is a lack of experimental confirmations of theoretical assumptions. This paper reviews external non-involute shapes, their operating characteristics and possibilities of use compared to involute gears. Established criteria, such as Hertzian pressure, oil film thickness, bending stress at the root of the tooth, contact temperature, and gear noise, were used for assessment. The results of analytical studies and experimental research on S-gears are presented in more detail. S-gears have a higher surface durability and a lower heat load when compared to involute gears. The usability of non-involute gears is increasing with the development of new technologies and materials. However, the advantages of non-involute shapes are not so significant that they could easily displace involute gears, which are cheaper to manufacture.
Keywords: cikloidno ozobje; gearing load capacity; neevolventni zobniki; non-involute gears; nosilnost ozobja; Novikov gears; Novikov ozobje; path of contact; profil boka zoba; S-gears; S-zobniki; tooth profile; ubirnica